Integrasi Model Pembelajaran Kooperatif Tipe STAD dalam Pembelajaran IPS untuk Mengembangkan Karakter di SD Kelas Tinggi - Angel Dwi Septianingrum; Andriani Safitri (Peneliti.net, 2023)
The purpose of this study was to determine the integration of the use of the STAD type cooperative learning model in social studies learning in order to develop the character of students in high school grades. The research method used is descriptive qualitative by conducting a literature study. The conclusion of this study is that the use of the STAD type of cooperative learning model in social studies learning can improve the characteristics of high-grade elementary school students, especially in the character of gotong royong or the willingness to work together. This happens because the STAD type supports students to actively work in groups that have members with different backgrounds so as to increase empathy, tolerance, and the ability to work together in groups. In addition, social studies in high grades are also sustainable in developing the character of students in the community, including the school environment.